Ensaios de filtração em solos com geotêxteis - Spada, Jorge Luís Goudene (1991)
The present work is a study of geotextile filter behaviour. Initially, it presents the usual parameters to describe the geotextiles characteristics, the involved phenomena in the geotextile-soil interaction and the more accepted criteria for geotextile filter selection. Supported by previous researches, a filtration apparatus was developed for laboratory tests, based on the Gradient Ratio methodology, proposed by CALHOUN (1972). This apparatus was employed to perform eighteen long term filtration tests, during which ten different combinations of geotextile-soil were tested. ln order to be compared with geotextile filters, it was also tested a paper filter and a natural filter. The results of the tests showed that geotextile performed well. The comparison of tests results with the above mentioned criteria indicated that such criteria were conservative in this study. It was verified that special care should be taken to avoid the appearence of ferruginous sediments in the water during long term filtration tests.